Multipliers : how the best leaders make everyone smarter - Wiseman, Liz; McKeown, Greg (Harper Business, 2010)
"A thought-provoking, accessible, and essential exploration of why some leaders (called "Diminishers") drain capability and intelligence from their teams while others (called "Multipliers") amplify it to produce better results"--Provided by publisher